2016
DOI: 10.1038/srep21735
|View full text |Cite
|
Sign up to set email alerts
|

The miR-34a-LDHA axis regulates glucose metabolism and tumor growth in breast cancer

Abstract: Lactate dehydrogenase A (LDHA) is involved in a variety of cancers. The purpose of this study was to investigate the expression, prognostic roles and function of LDHA in breast cancer. We found that LDHA was upregulated in both breast cancer cell lines and clinical specimens using quantitative real-time PCR (qRT-PCR). Immunohistochemistry (IHC) analysis of tissue microarrays (TMAs) showed that high LDHA expression was associated with cell proliferation, metastasis and poor patient overall survival (OS) and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 47 publications
2
83
0
Order By: Relevance
“…We found that miR-34a expression was decreased in T cells, which contributed to the increase in LDHA in human GC TILs. Several studies have revealed that LDHA is one of the target genes of miR-34a in different cancer tissues including breast cancer and colorectal cancer (CRC) [15,16,21]. Our results also indicated a similar outcome in that miR-34a downregulated LDHA expression in T cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We found that miR-34a expression was decreased in T cells, which contributed to the increase in LDHA in human GC TILs. Several studies have revealed that LDHA is one of the target genes of miR-34a in different cancer tissues including breast cancer and colorectal cancer (CRC) [15,16,21]. Our results also indicated a similar outcome in that miR-34a downregulated LDHA expression in T cells.…”
Section: Discussionsupporting
confidence: 77%
“…To investigate the mechanism of increased LDHA in T cells, we detected the expression of miR-34a, which is reported to downregulate LDHA expression by targeting its 3' UTR [15,16]. miR-34a was significantly decreased in GC TILs and peripheral T cells compared to those from healthy controls (Fig.…”
Section: Decreased Expression Of Mir-34a Was Responsible For Increasementioning
confidence: 99%
“…MiRNAs play great important roles in breast cancer glycolysis [14][15][16][17][18][19]. In this study, we found that miR-216b-5p, miR-33a-5p and miR-122-5p inhibited glycolysis via targeting HK2, LDHA and PKM2.…”
Section: Discussionmentioning
confidence: 62%
“…There was no significant difference for PKM2 mRNA in the breast cancer with miR-122-5p or the miRNA control transfection, but, PKM2 protein showed down-regulation in the cells. HK2 was regulated by miR-143 [24], miR-155 [25], miR-199a-5p [26], miR-29b [27,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], miR-140-5p in various cancers like bladder cancer, liver cancer and prostate cancer. LDHA was regulated by miR-383, miR34a, miR-122, miR-30a-5p and other miRNAs in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic aggression of TNBC is associated with overexpression of lactic acid dehydrogenase (LDH), production of lactate and a subsequent acidic pH which circumscribes tumors in the absence or presence of oxygen (Warburg effect). TNBC cells convert pyruvate to lactic acid via LDHA (Figure 1), the extent of which is associated with metastatic invasiveness, Ki-67 proliferation marker and poor clinical outcome (1, 2). Elevated glycolytic production of lactate is observed in diverse cancers where greater LDHA expression correlates to poor survival rates, greater tumor size, advanced clinical stage, Gleason scores, histological grade and relapse (3, 4).…”
mentioning
confidence: 99%